Echoes of the past: prevalence and correlates of PTSD among formerly abducted youths in northern Uganda: findings from the WAYS study - Bernard Omech; Kennedy Amone-P'Olak; Adrian Ivan Kakinda; Henry Kibedi (General Psychiatry, 2022)
Background Post-traumatic stress disorder (PTSD) has considerable and persistent effects on survivors of war, particularly in postconflict areas. Yet, evidence on what keeps survivors on the path of PTSD remains scarce.Aims The current study aimed to assess the prevalence and correlates of PTSD symptoms among the war-affected population in northern Uganda.Methods Data from 476 war-affected youths (aged 20–27 years) who had participated in a longitudinal cohort study were analysed to describe the enduring associations of background and postwar environmental risk factors with PTSD symptoms. The Impact of Event Scale-Revised was used to evaluate symptoms of PTSD. Descriptive statistics were used to compute background and postwar environmental correlates. Binary logistic regression analyses were fitted to assess the magnitude of the effects of the correlates on PTSD symptoms.Results Background and postwar environmental factors (eg, sexual abuse and injury in captivity) were significantly associated with PTSD symptoms. Postwar environmental factors associated with PTSD symptoms included postwar hardships, stigma/discrimination, chronic illness, community relations, family acceptance and general functioning, among others. The odds ratios (ORs) for post-war hardships were 2.41 (95% confidence interval (CI): 1.63 to 3.56) and 2.90 (95% CI: 2.03 to 4.14) for high and severe PTSD, respectively. For stigma/discrimination, compared with higher scores, the ORs were 3.38 (95% CI: 2.22 to 5.17) and 4.12 (95% CI: 2.69 to 6.30) for high and severe PTSD symptoms, respectively.Conclusions Background and postwar environmental stressors exacerbate the severity of PTSD symptoms in survivors of war and should form the basis for interventions to alleviate the toxic effects of war on survivors.